Promoting sustainability through corporate social responsibility: Malaysia environmental law initiative - Mustafa, Maizatun; Mohd Rusli, Mohd Hazmi; Mohamad, Nor Asiah; Ariffin, Mariani (2013)
Corporate Social Responsibility is the way businesses manage their activities to produce an overall positive impact through economic, environmental and social actions. Previously, Malaysia’s corporate environmental management strategies were largely reactive in nature, such as through the compliance of legal emission standards. However, due to various factors including that of climate change commitment, there is now a shift in Malaysia towards green markets which foster a more proactive stance on environmental management. Considering that environmental sustainability is one of the key components within the eco-friendly business practices, it is the aim of this article to look into some recent developments within the law in Malaysia that promote strategies aiming at encouraging companies to find solutions to their environmental impact and curbing carbon emission.